RAINBOW magic THE JEWEL FAIRIES : Scarlett the Garnet Fairy - Meadows, Daisy; Daisy Meadows (New York Scholastic Inc., 2005)
"Kirsty and Rachel are off to Buttercup Farm for the day! When they arrive, they notice that things aren't right--farm tractors are the size of toy cars, and all the sheep have shrunk down to the size of mice! Scarlett the Garnet Fairy controls magic that makes things grow and shrink, but without her magic jewel, everything is the wrong size. Best friends Kirsty and Rachel have already helped India the Moonstone Fairy get her jewel back--now can they help Scarlett the Garnet Fairy find her magic jewel before it's too late?
English
Keywords: Juvenile fiction; Fantasy